2019
DOI: 10.1080/00498254.2018.1559376
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic fate and effects of 2-Bromophenol in male Sprague–Dawley rats

Abstract: 2 1. The metabolic fate and urinary excretion of 2-bromophenol, a phenolic metabolite of 3 bromobenzene, was investigated in male Sprague Dawley rats following single intraperitoneal 4 doses at either 0, 100 or 200 mg/kg. 5 2. Urine was collected for seven days and samples analysed using 1 H NMR spectroscopy, 6 inductively coupled plasma (ICP)MS, and UPLC-MS. 7 3. 1 H NMR spectroscopy of the urine samples showed that, at these doses, 2-bromophenol had 8 little effect on endogenous metabolite profiles, supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…When the untargeted LC/MS data obtained for each of the time period collections (pre-dose, and 0-3, 3-8, and 8-24 h post-dose) were analyzed in this way, differences were readily observed between control and IV dosed samples by PCA (Figure 1 for positive ESI and Figure S2 for negative ESI). However, despite the clear detection of gefitinib and its metabolites in the urine obtained previously [14], and unlike the situation reported for a number of other compounds, e.g., [30][31][32][33][34], none of the ions associated with them contributed to the observed PCA separation. Thus, as shown in Figure 1A and B for the positive ion data, the removal of all of the previously identified ions associated with gefitinib and its metabolites [14] had no effect on the observed PCA score plot.…”
Section: Untargeted Analysis Of Urine Including Gefitinib and Metabol...contrasting
confidence: 86%
See 3 more Smart Citations
“…When the untargeted LC/MS data obtained for each of the time period collections (pre-dose, and 0-3, 3-8, and 8-24 h post-dose) were analyzed in this way, differences were readily observed between control and IV dosed samples by PCA (Figure 1 for positive ESI and Figure S2 for negative ESI). However, despite the clear detection of gefitinib and its metabolites in the urine obtained previously [14], and unlike the situation reported for a number of other compounds, e.g., [30][31][32][33][34], none of the ions associated with them contributed to the observed PCA separation. Thus, as shown in Figure 1A and B for the positive ion data, the removal of all of the previously identified ions associated with gefitinib and its metabolites [14] had no effect on the observed PCA score plot.…”
Section: Untargeted Analysis Of Urine Including Gefitinib and Metabol...contrasting
confidence: 86%
“…There was also a third group of metabolites where, although detectable in both the 0-3 and 3-8 h collections, the maximum amounts observed were in the 8-24 h urine, typified by the O-desmethyl metabolite M7 (M523595). While readily detected using conventional methods, the absence of these compounds as discriminating features in the PCA analysis is more disappointing when compared with some earlier work, e.g., [23,[30][31][32][33][34]. However, given that the removal of gefitinib-related features from the PCA had no discernible effect on the score plots for PCs 1 and 2, it is unsurprising that the examination of the data confirmed that none of the top 100 discriminating ions were gefitinib-related.…”
Section: Untargeted Analysis Of Urine Including Gefitinib and Metabol...mentioning
confidence: 80%
See 2 more Smart Citations
“…For example, a previous study has shown that 2,4,6-TBP is a typical substrate of SULTs (16). UPLC-MS analysis of urine samples has identified the sulfate and glucuronide metabolites of 2-BP (17). Therefore, glucuronidation and sulfation are the main elimination pathways of BPs in humans.…”
Section: Discussionmentioning
confidence: 99%